PENGARUH PENGGUNAAN ALAT PERAGA BLOK PECAHAN TERHADAP HASIL BELAJAR PADA MATA PELAJARAN MATEMATIKA KELAS III SEKOLAH DASAR - Karunia, Indah; Destiniar, Destiniar; Handayani, Widya (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to determine the effect of using fraction block teaching aids on student learning outcomes on class III Mathematics subjects at SD Negeri 89 Palembang. The method used was an experiment, namely True Experimental design, Posttest Only Control Design type, while the research subjects were class III students at SD Negeri 89 Palembang. Class III A as the experimental class and III B as the control class with 21 students in each class. Data collection techniques are tests and documentation. The data analysis technique is the Independent T-test. Based on the research results, the average Posttest score obtained from learning using fractional block teaching aids was 69.14 and for learning that did not use fractional block teaching aids it was 65.48. From hypothesis testing it was obtained (4,900>0.3044), with a significance level of 0.05. It can be declared rejected or accepted. Thus, the fraction block teaching aid has an effect in improving student learning outcomes on class III Mathematics subjects at SD Negeri 89 Palembang.